Šta da Ti kažem... – tekstualni grafiti u Hrvatskoj - Błachowicz-Wolny, Anna; Błachowicz, Ewa (Słowo. Studia językoznawcze, 2017)
The article is a review and analysis of the language used by graffiti writers who comment on and ironize the existing social, political and cultural situation in Croatia. The variety of graffiti forms, its structure and message play an important role in shaping the city space and show the reaction to the general social reality. The inscriptions refer to aphorisms, sayings. They enter into a dialogue with the mass culture. The classification of material, compiled for the purpose of the analysis, shows the attitudes and emotions of senders and can be perceived as a record of current views of Croatian society.